Analisis Efektivitas Kebijakan Publik dalam Meningkatkan Kualitas Pelayanan Publik di Indonesia - Firmansyah Firmansyah; Holijah Holijah (SPT. haria Journal and Education Center Publishing, 2026)
Public policy is a crucial instrument used by the government to improve the quality of public services. This study aims to analyze the effectiveness of public policy in improving the quality of public services in Indonesia, the factors supporting and inhibiting its implementation, and provide strategic recommendations. The study employed qualitative methods with a literature review approach. The results indicate that bureaucratic reform, service digitization, and strengthening governance have had a positive impact on the quality of public services, although various obstacles remain, such as limited human resources, uneven infrastructure, and low digital literacy.